Experimental investigation of the effect of bypass inlet on flow boiling in a mini/micro-channel. (January 2020) - Loganathan, Raamkumar; Mohiuddin, Ahmed; Gedupudi, Sateesh
Abstract: The present work reports the findings from an experimental study on the effect of bypass inlet on the performance of flow boiling of water in a copper mini/micro-channel of dimension 2.5 mm wide x 0.6 mm deep x 25 mm long. The mass fluxes considered were 430 kg/m 2  s, 640 kg/m 2  s and 850 kg/m 2  s and the heat flux was in the range 87–548 kW/m 2 . The results show a significant increase in heat transfer coefficient with the increase in bypass ratio for the subcooled boiling conditions and the enhancement decreases with the increase in the exit quality. An increase in pressure drop was also noticed due to the bypass inlet. The study indicates potential for further investigation and optimization.